1990
DOI: 10.1007/bf00053426
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and treatment of Raynaud's phenomenon

Abstract: The pathogenetic theories and treatment of Raynaud's phenomenon are reviewed. In primary Raynaud's disease, most evidence supports a local defect at the digital artery level, with vasoconstriction or vasospasm of the digital arteries inducing the color changes. Normal sympathetic activity, low transmural arterial distending forces, and serotonin may be associated factors in the production of vasospastic attacks. In Raynaud's phenomenon, persistent vasoconstriction, thickened vessel walls, increased blood visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…α 1 -Adrenergic receptor (AR) antagonists are widely used as antihypertensive drugs, for the treatment of benign prostate hyperplasia, and off-label for the treatment of Raynaud’s syndrome[ 1 3 ]. Moreover, the α 1 -AR antagonist prazosin has recently been evaluated in clinical trials in patients with post-traumatic stress disorders and nightmares[ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…α 1 -Adrenergic receptor (AR) antagonists are widely used as antihypertensive drugs, for the treatment of benign prostate hyperplasia, and off-label for the treatment of Raynaud’s syndrome[ 1 3 ]. Moreover, the α 1 -AR antagonist prazosin has recently been evaluated in clinical trials in patients with post-traumatic stress disorders and nightmares[ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two subtypes are described, primary Raynaud’s which is not associated with any other illness and secondary Raynaud’s phenomenon, where vasospasms are associated with another disease, commonly autoimmune diseases, mixed connective tissue disease and scleroderma. Pathogenesis of primary Raynaud’s phenomenon is not fully understood but vascular, intravascular and neural mechanisms are proposed [ 6 ],[ 11 ]. Of the neural mechanisms, central impairment of the autonomic function resulting in Raynaud’s phenomenon is suggested by the research done by Koszewicz et al [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mallipeddi et al concluded that primary Raynaud’s phenomenon is associated with sympathetic denervation in chronic autonomic failure [ 10 ]. Sympathetic over-activity provoking vasospasm by exaggerated vascular response is also suggested as one of the mechanisms causing Raynaud’s phenomenon [ 11 ],[ 13 ]. Hyperactivity of the α2c adrenorecepters is also postulated as one of the mechanisms [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…• There is predominance of α 2 -adrenoceptors in digital arteries and dermal arterioles 119,120 • Patients with RP are hypersensitive to the vasoconstrictor effects of α 2 -adrenoceptor agonist clonidine, but not to α 1 -adrenoceptor agonist phenylephrine 18,121,122 • α 2 -adrenoceptor antagonist yohimbine increases finger blood flow and decreases vascular resistance during reflex sympathetic vasoconstriction caused by body cooling 123 Beta-adrenergic blockade…”
Section: Increased Adrenergic Activitymentioning
confidence: 99%